2019
DOI: 10.1107/s2052520619009156
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli-responsive aggregation-induced fluorescence in a series of biphenyl-based Knoevenagel products: effects of substituent active methylene groups on π–π interactions

Abstract: A series of three biphenyl‐based Knoevenagel products (denoted 1a, 1b, 1c) with active methylene groups has been synthesized. Compounds 1a and 1b show strong solid‐state fluorescence, whereas 1c displays low emission. Effects of substituent groups in condensed phase packing of the molecules have been investigated and correlated with their photophysical properties. Interestingly, compound 1a exhibits mechanofluorochromism with emission color changes from yellow to green (wavelength shift of 40 nm) after mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Solid-state luminescence, pH-dependent fluorescence sensing, and mechano-fluorochromic behavior of the 1a-N needle form were discussed in our previous report . We measured the solid-state absolute photoluminescence quantum yield of the crystal and ground powder of both polymorphs.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Solid-state luminescence, pH-dependent fluorescence sensing, and mechano-fluorochromic behavior of the 1a-N needle form were discussed in our previous report . We measured the solid-state absolute photoluminescence quantum yield of the crystal and ground powder of both polymorphs.…”
Section: Resultsmentioning
confidence: 93%
“…Out of them, the biphenyl-dicyano derivative labeled as 1a (Figure a) exhibits solid-state fluorescence, mechano-fluoro-chromism, as well as pH-dependent fluorescence quenching. Herein, we have explored the nanomechanical properties of the reported needle-shaped polymorph of 1a (labeled 1a-N ) and a newly discovered block-shaped polymorphic form ( 1a-B ). The two polymorphic forms exhibit distinct emission colors in the solid state under UV light at 365 nm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…52,53 Subtle modifications in intermolecular interactions such as hydrogen bonding, halogen bonding, π⋯π interactions, and C-H⋯π interactions produce a different molecular arrangement and a drastic change in their optoelectronic properties. In a recent report, Sarma et al 54 synthesized a few biphenyl based donor-π-acceptor organic fluorophores that showed AIE along with mechanofluorochromism. As an extension to that, a dimorphic biphenyl based Michael addition product was synthesized.…”
Section: Introductionmentioning
confidence: 99%